Severe ectopic Cushing syndrome in a transgender man with a metastatic gastrinoma and an adrenal tumor—A case report and review of the literature - Wydra, Arnika; Cylke-Falkowska, Karolina; Czajka-Oraniec, Izabella; Kolasińska-Ćwikła, Agnieszka; Ćwikła, Jarosław; Zgliczyński, Wojciech; Stelmachowska-Banaś, Maria (Frontiers in Endocrinology, 2023)
A 38-year-old transgender male with advanced metastatic functional pancreatic neuroendocrine neoplasm (PanNEN)- gastrinoma was admitted to the Department of Endocrinology due to severe ACTH-dependent hypercortisolemia. An ectopic production of ACTH by PanNEN was suspected. The patient was qualified for bilateral adrenalectomy after preoperative treatment with metyrapone. Finally, the patient underwent resection of the left adrenal gland with the tumour only, which surprisingly resulted in significant decrease in ACTH and cortisol levels leading to clinical improvement. Pathology report revealed an adenoma of the adrenal cortex with positive ACTH staining. The result of the simultaneous liver lesion biopsy confirmed a metastatic NEN G2 with positive ACTH immunostaining as well. We looked for a correlation between gender-affirming hormone treatment and the onset of the disease and its rapid progression. This may be the first case describing the coexistence of gastrinoma and ectopic Cushing disease in a transsexual patient.